Sir3 and Epigenetic Inheritance of Silent Chromatin in Saccharomyces cerevisiae - Motwani, Tina (American Society for Microbiology, 2012)
Epigenetic mechanisms maintain the specific characteristics of differentiated cells by ensuring the inheritance of gene expression patterns through DNA replication and mitosis. We examined the mechanism of epigenetic inheritance of Sir protein-dependent transcriptional silencing in Saccharomyces cerevisiae by examining gene expression and molecular markers of silencing at the silent mating type loci under conditions of limiting Sir3 protein. We observed that silencing at HMR, as previously reported for HML, is epigenetically inherited. This inheritance is accompanied by an increased ability of previously silenced cells to retain or recruit limiting Sir3 protein to cis-acting silencer sequences. We also observed that the low H4-K16 histone acetylation and H3-K79 methylation associated with a silenced HMR locus persist in recently derepressed cells for several generations at levels of Sir3 insufficient to maintain these marks in long-term-derepressed cells. The unique ability of previously silenced cells to retain Sir3 protein, maintain silencing-specific histone modifications, and repress HMR transcription at levels of Sir3 insufficient to mediate these effects in long-term-derepressed cells suggests that a cis-acting, chromatin-based mechanism drives epigenetic inheritance at this locus.